How long before care do children wait in an emergency department of a third-level pediatric hospital in Peru? - Gálvez-Arévalo, Ricardo A. (2023)
Introduction: The application of an adequate system of prioritization of emergency care is essential to avoid more significant morbidity and mortality in critically ill pediatric patients. It is recommended that priority I, II, III, IV, and V cases have a maximum waiting time of 5, 15, 30, 60, and 120 minutes, respectively. This study aims to describe emergency waiting times according to care as a priority in a tertiary health hospital in Peru. Methods: This is a descriptive study, and the Emergency care records were used, between 2018 and 2022. Results: A total of 45,015 records of pediatric patients were included. 28.0% of cases with priority I, 86.9% of cases with priority II, 58.0% with priority attention III, 87.2% with priority attention IV, and 96.1% with priority V had the recommended wait time for your priority type. Conclusion: We found that the percentages of cases attended to before the recommended maximum wait times have not yet reached the values recorded in most previous studies. Studies must identify the factors associated with greater or lesser waiting times in the Emergency Department.